An anatomical and systematic study of the family Mesosauridae (reptilia : proganosauria) with special reference to its associated fauna and palaeoecological environment in the Whitehill Sea - Oelofsen, B. W.(Burger Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, [1981?].